HISTORY OF DEVELOPMENT OF INTERNATIONAL LAW (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
definition of the concept of "international law" is one of the most important tasks of the science of international law. If, state and law if the science of theory studies the phenomena characteristic of the national legal system of states, and the science of international law is specific to interstate or international relations in a broader sense examines the legal features of events and processes. This is it the article describes the history of the development of international law in detail.